2019
DOI: 10.3389/fgene.2019.00440
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Landscape of Crossover Interference in the Desert Tree Populus euphratica

Abstract: Crossover (CO) interference is a universal phenomenon by which the occurrence of one CO event inhibits the simultaneous occurrence of other COs along a chromosome. Because of its critical role in the evolution of genome structure and organization, the cytological and molecular mechanisms underlying CO interference have been extensively investigated. However, the genome-wide distribution of CO interference and its interplay with sex-, stress-, and age-induced differentiation remain poorly understood. Multi-poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Moreover, we found that there existed a significant difference of CO interference between the two parents in that the negative interference in the female was stronger than in the male. The phenomenon of extensive occurrences of CO interference was also observed by Wang et al [63] in P. euphratica. The difference of interference strength between two sexes in Populus was similar to the results from studies in mice and cattle [34,39], and even in humans [64].…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, we found that there existed a significant difference of CO interference between the two parents in that the negative interference in the female was stronger than in the male. The phenomenon of extensive occurrences of CO interference was also observed by Wang et al [63] in P. euphratica. The difference of interference strength between two sexes in Populus was similar to the results from studies in mice and cattle [34,39], and even in humans [64].…”
Section: Discussionsupporting
confidence: 71%
“…This indicates that the processes underlying crossover interference may be evolutionarily conserved. We should note that despite the general mechanism of crossover interference acting at the whole-genome level, there are exceptions where crossover interference has variable intensities and distributions in different regions of a chromosome, such as observed in budding yeast and in Populus euphratica ( Malkova et al , 2004 ; Wang et al , 2019 ).…”
Section: Discussionmentioning
confidence: 98%